(untitled) (Tabanque. Revista Pedagógica, 2018)
In 2010 the socio educational department of the Castilla y León Symphonic Orchestra and the Antonio Allué Morer primary school of Valladolid set up an educational project based on the practice of music. This initiative, leader in the context of Spanish state school, arouse with the aim of providing harmonious co-existence and integration in a student community of disadvantaged situation and in some cases at risk of social exclusion. The development of this project has proved how beneficial this different approach in education can be and it has also highlighted the difficulties to put it in practice within the current education system. This article intends to analyse some issues derived from the collaboration among different institutions in the education task. Political, administrative and school organization aspects on one hand and the social consideration of music and its relevance in the school curriculum on the other, make us reflect upon the sense in the current basic education and how some social groups can access to it.